1996
DOI: 10.1901/jaba.1996.29-11
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Problem Difficulty and Reinforcer Quality on Time Allocated to Concurrent Arithmetic Problems

Abstract: Students with learning difficulties participated in two studies that analyzed the effects of problem difficulty and reinforcer quality upon time allocated to two sets of arithmetic problems reinforced according to a concurrent variable-interval 30-s variable-interval 120-s schedule. In Study 1, high- and low-difficulty arithmetic problems were systematically combined with rich and lean concurrent schedules (nickels used as reinforcers) across conditions using a single-subject design. The pairing of the high-di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
2

Year Published

1997
1997
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(47 citation statements)
references
References 26 publications
1
44
2
Order By: Relevance
“…These findings have encouraged applied researchers to examine the influence of various dimensions of reinforcement and the matching law in clinical and educational settings. Several investigations have been conducted with students diagnosed with severe emotional, behavioral, and learning disorders on the effects of response effort and reinforcement rate, quality, and delay on allocation to concurrently available academic tasks (Dixon & Cummings, 2001;Mace, Neef, Shade, & Mauro, 1996;Neef & Lutz, 2001;Neef, Mace, & Shade, 1993;Neef, Mace, Shea, & Shade, 1992;Neef, Shade, & Miller, 1994). Among the dimensions studied was quality of reinforcement, defined as stimuli that were reliably selected as highly preferred in stimulus preference assessments.…”
mentioning
confidence: 99%
“…These findings have encouraged applied researchers to examine the influence of various dimensions of reinforcement and the matching law in clinical and educational settings. Several investigations have been conducted with students diagnosed with severe emotional, behavioral, and learning disorders on the effects of response effort and reinforcement rate, quality, and delay on allocation to concurrently available academic tasks (Dixon & Cummings, 2001;Mace, Neef, Shade, & Mauro, 1996;Neef & Lutz, 2001;Neef, Mace, & Shade, 1993;Neef, Mace, Shea, & Shade, 1992;Neef, Shade, & Miller, 1994). Among the dimensions studied was quality of reinforcement, defined as stimuli that were reliably selected as highly preferred in stimulus preference assessments.…”
mentioning
confidence: 99%
“…The behaviour selected is typically the behaviour that: (1) is reinforced on the densest schedule (Horner & Day, 1991;Neef, Mace, Shea, & Shade, 1992); (2) results in the highest quality of reinforcement (Neef et al, 1992;Peck et al, 1996); (3) results in the greatest amount of reinforcement Martens, 1990;Martens, Halperin, Rummel, & Kilpatrick, 1990;Martens & Houk, 1989;Martens, Lochner, & Kelly, 1992); or (4) has the shortest delay to reinforcement (Horner &Day, 1991: Neef, Mace, &Shade, FCT andChoice Making 259 1993). In addition, the response that requires the least amount of effort to display is more likely to occur than a response that requires more effort (Horner & Day, 1991;Mace, Neef, Shade, & Mauro, 1996;Richman et al, 2001). These dimensions of reinforcement may also interact to affect which behaviour will be displayed (Neef & Lutz, 2001;Neef et al, 1992;Neef, Shade, & Miller, 1994).…”
Section: Blending Functional Communication Training and Choice Makingmentioning
confidence: 99%
“…Several applied studies have demonstrated that when students are given a choice between two tasks, they distribute their time between these tasks at a rate equivalent to the rate of reinforcement provided for these tasks (Mace, McCurdy, & Quigley, 1990;Mace, Neef, Shade, & Mauro, 1996;Martens & Houk, 1989;Martens, Lochner, & Kelly, 1992;Neef, Mace, & Shade, 1993;Neef, Mace, Shea, & Shade, 1992). This match between a respondent's behavior and the level of reinforcement provided is described by Herrnstein's (1961) Matching Law.…”
Section: Reinforcement Proceduresmentioning
confidence: 99%
“…For another student, reinforcement delay influenced choice behavior more than quality or rate of reinforcement. In a similar study, Mace et al (1996) investigated the interaction between reinforcer quality, rate, and problem or assignment difficulty. Results show that choice behaviors were more influenced by quality and rate of reinforcement than assignment difficulty.…”
Section: Behavior Psychology In the Schoolsmentioning
confidence: 99%